Impacts of temperament on Nellore cattle: Physiological responses, feedlot performance, and carcass characteristics - Francisco, C. L. [UNESP]; Resende, F. D.; Benatti, J. M.B.; Castilhos, A. M. [UNESP]; Cooke, R. F.; Jorge, A. M. [UNESP] (Oxford University Press (OUP), 2015)
Forty-four feedlot-finished Nellore cattle were used to evaluate the impacts of temperament on performance, meat and carcass traits, and serum concentrations of hormones, proteins, enzymes, and immunoglobulins. Individual temperament was assessed at feedlot entry (d 0), 67 d, and 109 d, utilizing chute score (CS; 5-point scale) and exit velocity (EV). Temperament scores were calculated averaging CS and EV scores, and cattle were subsequently classified according to their temperament (an average of ≤3 = adequate temperament [ADQ], or an average of >3 = excitable temperament [EXC]). At the end of the experiment (d 109), all 44 animals were slaughtered, and 16 were randomly selected for final empty body weight (EBW) estimation. Blood samples were collected at 0, 67, and 109 d and analyzed for serum variables (cortisol, insulin, haptoglobin, total protein, lactate, creatinine kinase [CK], lactate dehydrogenase [LDH], and IgA). The incidence of carcass bruises was verified immediately after the hide was removed. Carcass pH was obtained at 0 and 24 h postmortem. Samples of the LM were collected for meat quality analyses. Cattle classified as ADQ had greater final BW (P = 0.03), final EBW (P = 0.02), metabolic weight (P = 0.03), ADG (P = 0.02), feed efficiency (P = 0.03), HCW (P = 0.02), cold carcass weight (P = 0.02), and LM area (P < 0.01) compared to that of the EXC cohorts. Cattle classified as ADQ tended to have a lower percentage of cooler shrink (P = 0.06) compared to that of EXC cattle. No temperament effects were detected for initial BW (P = 0.70), DMI (P = 0.14), cold dressing percentage (P = 0.98), or backfat thickness (P = 0.29). Cattle classified as ADQ had greater marbling (P = 0.02) and meat fat content (P = 0.05) compared with that of EXC cattle. No temperament effects (P > 0.05) were detected for unsaturated fatty acid (UFA), SFA, MUFA, PUFA, and n-6:n-3 ratio. For blood parameters, EXC cattle had greater values of cortisol (P = 0.04) and haptoglobin (P = 0.05) and tended (P = 0.06) to have reduced serum insulin concentration compared with ADQ cattle. Both temperament groups had similar serum concentrations of IgA (P = 0.25) and total protein (P = 0.84). Cattle classified as EXC presented greater amounts (P = 0.05) of carcass bruises. In conclusion, an EXC temperament impaired feedlot performance, carcass characteristics, and meat quality traits in finishing Nellore cattle.
Keywords: Acute-phase protein; Beef cattle; Bruises; Cortisol; Meat quality; Performance